Pengaruh Pengalaman Kerja, Tingkat Pendidikan dan Penilaian Prestasi Kerja terhadap Kinerja Karyawan pada PT Laju Niaga Gemilang - Maytasari, Priya Eka; Riski Ulan Sari (BUDGETING : Journal of Business, Management and Accounting, 2025)
This research aims to determine the influence of work experience, education level, and job performance appraisal on employee performance at PT. Laju Niaga Gemilang.This research uses a quantitative method.The sampling technique used is saturated sampling.The sample in this study consisted of 50 employees, and the object of this research was PT. Laju Niaga Gemilang.The data collection technique involved the distribution of questionnaires, and the obtained data were analyzed using the multiple linear regression analysis method with the help of SPSS 26 software.The results of this study indicate that partially, the variable of work experience (X1) has a positive and significant effect on employee performance (Y), the level of education (X2) has a positive and significant effect on employee performance (Y), and the performance appraisal (X3) has a positive and significant effect on employee performance (Y).Then, simultaneously, there is a positive and significant influence between work experience (X1), education level (X2), and performance appraisal (X3) on employee performance (Y) at PT. Laju Niaga Gemilang.   Keywords: Employee Performance, Work Experience, Education Level, Job Performance Appraisal